Revolusi budaya digitalisasi informasi: dampaknya bagi pustakawan dalam mengelola pengetahuan - Endang Fatmawati (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
The shift in the culture of information digitization affects librarians in managing knowledge. Moreover, information becomes the main door to gain knowledge so that technology literacy and information access competency becomes very important. The shifting of information sources from printed form to digital is due to the presence of digital reproduction means. Librarians must be able to manage knowledge holistically in creating community knowledge. Digital media transfer needs to be done as an effort to maintain the library collection. Knowledge is considered the most strategically important resource and learning capability for library. Social media is also seen as an effective outreach tool, helping librarians promote their library and connect more deeply with the broader library community.